PENERAPAN STRATEGI PEMBELAJARAN INKUIRI SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR TEORI DASAR-DASAR PENGELASAN KELAS XII DI SMK KRISTEN 1 KLATEN TAHUN AJARAN 2013/2014 - Sumarwan Sumarwan; Samsul Hadi (Jurnal Taman Vokasi, 2013)
The purpose of this research was to know the learning process and underlying principles of welding achievement students of with problem based learning. This research is Classroom Action Research. The subjects in this research were students of class XII which is 21 students. The data collecting technique in this research was done by using observation, and tests. The result of this research showed an increase in the learning process and achievement of students in the learning process. This is indicated by an increase in percentage of students learning process on the first cycle is 74%, while on the second cycle increased to 79%, and while on the third cycle increased to 85%. The percentage of the KKM students also increased, first cycle at 28,57% increased to 33,33% in the second cycle, and the third cycle again increased to 76,19%.